Insegnare chimica fisica con dashboard sviluppate in Python - Lombardo, Renato (Chimica nella Scuola, 2024)
Mathematical models and graphs are essential in chemistry and other scientific disciplines, but their complexity can hinder student understanding. Interactive applications, such as dashboards, can simplify complex data and enhance comprehension. Python and Plotly Dash are effective tools for creating custom dashboards tailored to specific teaching needs. These dashboards proved useful for students with limited mathematical background, and they can also support active learning strategies and develop cross-cutting skills like programming. However, their effectiveness depends on integration into the teaching process and teacher guidance.